Characterisation of regional strains in the western Saldania Belt and implications for the structural evolution of Pan-African Rocks in the Western Cape, South Africa - Rheeder, Christie George (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.